Բառապաշարի հարստացումը մայրենիի դասերին - Հասրաթյան, Ծովինար
В данной статье обсуждаются способы обогащения словарного запаса учеников некоторыми методами и средствами. В книгах по родному языку 5-6–х классов размещены некоторые задания с особыми пометками. Основа этих заданий - высказывание собственного мнения, словообразовательный анализ, выполнение требований при работе по орфографии, умение, навыки, словарный запас и самостоятельность. Новизна этого раздела целенаправлена на решение обсуждаемых проблем․ This article discusses ways of enrichment of the learners‘ vocabulary by means of some techniques and tools. In the books of the native language of the 5-6-th classes some tasks with special marks are placed.. A basis of these tasks - the statement of own opinion, the word-formation analysis, implementation of requirements during the work on spelling, ability, skills, vocabulary and autonomy. The novelty of this section is directed to the solution of the discussed problems.
Keywords: Հայոց լեզվի դասավանդման մեթոդիկա